Increased endothelial biomarkers are associated with HIV antiretroviral therapy and C-reactive protein among a African rural population in Limpopo Province, South Africa - Hanser, Sidney; Mphekgwana, Peter Modupi; Moraba, Mpho Matthias; Erasmus, Lourens; van Staden, Marlise (Frontiers in Public Health, 2022)
In Sub-Saharan Africa (SSA) endothelial dysfunction (ED) and chronic inflammation in the HIV-positive adults population who are on highly active antiretroviral therapy (HAART) are not fully explored. We determined the effect of HAART on chronic inflammation and ED among HAART-exposed adults in a rural setting. Weight and height were measured to quantify the body mass index (BMI). Lipid and Glucose levels were determined. C-reactive protein (CRP), L-selectin, soluble intercellular adhesion molecule (sICAM-1), and soluble vascular cell adhesion molecule (sVCAM-1) in serum samples were tested. The majority of the HAART-exposed group were on treatment for <5 years. Soluble intercellular adhesion molecules, sVCAM-1, L-selectin and CRP were elevated in the HIV-infected groups as compared to the control group. The multivariate analysis showed that HIV infection (HAART-naïve) associated with increased sICAM-1 (β = 0.350; 95% CI: 0.035–0.664, p = 0.029) and L-selectin (β = 0.236; 95% CI: 0.038–0.434, p = 0.019) but not sVCAM-1 (β = 0.009; 95% CI: 0.252–0.270, p = 0.468). The HAART-exposed group is associated with sVCAM-1 (β = 0.250; 95% CI: 0.015–0.486, p = 0.037) but not with sICAM-1- (β = 0.253; 95% CI: −0.083–0.590, p = 0.14) and L-selectin (β = 0.119; 95% CI: −0.016–0.253, p = 0.084). sVCAM-1 was associated with decreased alcohol consumption (β = −0.245; 95% CI: −0.469–0.021, p = 0.032) while L-selectin was associated with decreased total cholesterol (β = −0.061; 95% CI: −0.124–0.002, p = 0.05) and increased CRP (β = 0.015; 95% CI: 0.009–0.022, p < 0.001). Increased endothelial biomarkers were associated with HIV disease and HAART in a rural black adult population of African descent after controlling for CVD risk factors. Inflammation (as measured with CRP) may play an important role in endothelial activation. Further studies are needed to explore the association between endothelial dysfunction and inflammation especially among the HIV-positive population on HAART in similar settings.